ANALISIS PERSEPSI TENAGA PENDIDIK DI MTI CANDUANG TENTANG PRODUK BANK SYARI’AH - Muhammad Ilham; Sandra Dewi (JEBIMAN : Jurnal Ekonomi, Bisnis, Managemen dan Akuntansi, 2025)
Syariah banks exist to serve the needs of the community at large and the Muslim community in particular, including the financial needs of religious leaders like imams and teachers at Islamic schools and mosques. However, in reality, the majority Muslim population and its teachers at pondok pesantren are unable to demonstrate a good understanding of syariah banks and their products. The dominance of conventional banks over syariah banks has led to a lack of socialisation on the part of syariah banks, and a lack of knowledge of syariah banking products among the general population and especially among teachers in religious schools. Therefore, socialisation efforts should be made to increase the general public's familiarity with sharia-compliant banks.This study is an example of descriptive quantitative field research.This involves conducting research in the field by conducting interviews and surveys with students and teachers at MTI Canduang.Next, descriptive quantitative analysis will be used in the data collection process.This study's findings suggest that MTI Canduang teachers' knowledge of syariah-compliant banking products remains low due to insufficient outreach efforts on the part of syariah banks.